Service portability of networked appliances. - Moyer, S. (IEEE Communications magazine)
This document outlines an approach for delivering services to networked appliances using techniques that allow mobility of these services both in a conventional location-independent sense and between physical devices. Key requirements to address this market are identified and the document then goes on to present a technical solution to meet these requirements together with worked examples. It concludes with suggestions for further work